A micro-tattooing device for capsule endoscope using a Wood's metal triggering mechanism. (October 2019) - Joe, Seonggun; Lee, Dongkyu; Kang, Hyeongseok; Kang, Byungjeon; Park, Jong-Oh; Kim, Byungkyu
Abstract: The endoscopic tattooing procedure is essential before surgery in the gastroenterology practice. Because conventional tattooing is conducted by injecting biocompatible ink from outside the human body, a conventional tattooing device is not appropriate for use in the Capsule Endoscope (CE). A compact micro-tattooing device with an optimal triggering mechanism which can be enclosed in the CE is required. Therefore, A micro-tattooing device operated by two conical springs with a Wood's metal-based triggering module is proposed. Needle insertion and ink injection to the submucosal layer of the colon is actuated by triggering mechanism #1. When triggering mechanism #2 is activated, the needle is withdrawn to avoid scratching the internal lumen. Each triggering module is activated by the Joule heating of a Ni-Cr wire with low power consumption to accommodate the CE battery's small capacity. The in-vitro and ex-vivo tests were conducted to confirm the feasibility of the tattooing module. In the in-vitro test, the needle displacement was confirmed to be 3.3 mm. Using extracted porcine colon, the total tattooing procedure was conducted, and the injected ink in the submucosal layer was observed by hemisecting the specimen. Conclusively, the device achieved competitive results, both in terms of power consumption and space constraints.